1998
DOI: 10.1046/j.1365-2265.1998.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function in young adults with childhood and adulthood onset growth hormone deficiency

Abstract: Patients affected by GH deficiency have left ventricular systolic dysfunction at rest and during physical exercise, suggesting that GH plays a physiological role in maintaining normal cardiac performance in humans. Furthermore, no difference between childhood and adulthood onset GH deficient patients was found indicating that both group of patients have an impairment of cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 37 publications
3
65
0
1
Order By: Relevance
“…385 Although some studies suggest that cardiac dysfunction might be more severe in GH-deficient patients with childhood-onset disease than in patients with adult-onset disease caused by the lack of GH/ IGF-1 during growth and development of the heart, 391 this has not been seen consistently across other studies. 409 Short-term placebo-controlled studies have shown that GH replacement therapy in adult GH-deficient patients has an anabolic effect on cardiac structure, which results in an improvement in both diastolic and systolic function. 391,410,411 A few open-label studies have determined the long-term effects of GH replacement therapy on cardiac function.…”
Section: 394mentioning
confidence: 99%
“…385 Although some studies suggest that cardiac dysfunction might be more severe in GH-deficient patients with childhood-onset disease than in patients with adult-onset disease caused by the lack of GH/ IGF-1 during growth and development of the heart, 391 this has not been seen consistently across other studies. 409 Short-term placebo-controlled studies have shown that GH replacement therapy in adult GH-deficient patients has an anabolic effect on cardiac structure, which results in an improvement in both diastolic and systolic function. 391,410,411 A few open-label studies have determined the long-term effects of GH replacement therapy on cardiac function.…”
Section: 394mentioning
confidence: 99%
“…Last, the study populations are heterogeneous (childhood-onset or adulthood-onset GHD, age differences, and so forth), and this probably attenuates the observed effects of GH on systolic function, which is more strongly impaired in younger patients. 9,10,32,36,37 Diastolic function improved in a few published studies, 17,20 but the improvement was not significant in our meta-analysis, possibly owing to the small number of studies assessing the relevant parameters.…”
Section: Discussionmentioning
confidence: 66%
“…These differences were not confirmed in other studies or in GHD patients with adult-onset disease (19,20). Using equilibrium radionuclide angiography, we first reported LV systolic dysfunction at rest and at peak physical exercise in a group of GHD patients of less than 40 years of age, without any difference between childhoodand adulthood-onset GHD (21). These results were subsequently confirmed in another cohort of adult GHD patients in whom we did not find any difference between young patients (aged , 35 years) and middle-aged patients (36 -60 years) (22).…”
Section: Cardiac Involvement In Gh Deficiencymentioning
confidence: 69%